Integrated Measurement System of Postural Angle and Electromyography Signal for Manual Materials Handling Assessment - Halim, Isa; Hidayat, Adi Saptari; Abulais, Mohd Fairil; Padmanathan, Vinothini (International Journal of Integrated Engineering, 2021)
Ergonomics practitioners and engineers require an integrated measurement system which allows them to study the interaction of work posture and muscle effort in manual materials handling (MMH) tasks so that strenuous posture and muscle strain can be avoided. However, far too little attention has been paid to develop an integrated measurement system of work posture and muscle activity for assessing MMH tasks. The aim of this study was to develop and test a prototype of integrated system for measuring work posture angles and (electromyography) EMG signals of a worker who doing MMH tasks. The Microsoft Visual Studio software, a 3D camera (Microsoft Kinect), Advancer Technologies muscle sensors and a microcontroller (NI DAQ USB-6000) were applied to develop the integrated postural angle and EMG signal measurement system. Additionally, a graphical user interface was created in the system to enable users to perform work posture and muscle effort assessment simultaneously. Based on the testing results, this study concluded that the patterns of EMG signals are depending on postural angles which consistent with the findings of established works. Further study is required to enhance the validity, reliability and usability of the prototype so that it may facilitate ergonomics practitioners and engineers to assess work posture and muscle effort in MMH task.